Thermal-and fast-spectrum molten salt reactors for minor actinides transmutation. (1st December 2020) - Ashraf, O.; Tikhomirov, G.V.
Highlights: The transmutation performance of MAs in the critical SD-TMSR and SMSFR was investigated. The transmutation ratio of long-lived MAs was calculated using the SERPENT-2 Monte-Carlo code. The online reprocessing and refueling was applied during burnup. The dynamics of k eff, core reactivity, major isotopes inventory, and time evolution of MAs were investigated. The neutron energy spectrum shift with different MAs loadings was calculated. Abstract: The long-lived Minor Actinides (MAs): 237 Np, 241 Am, 243 Am, 243 Cm, 244 Cm, and 245 Cm are responsible for the effective dose and heat generation after direct disposal in deep geological structures. Thus, long-lived MAs represent a major burden of nuclear power. The long-lived MAs have not yet been utilized as nuclear fuel. Therefore, the transmutation of these MAs is proposed as an alternative to the direct final disposal. In the current work, we analyze and compare the MAs transmutation performance in the critical Single-fluid Double-zone Thorium-based Molten Salt Reactor (SD-TMSR) and Small Molten Salt Fast Reactor (SMSFR). We study the variation of the K eff and core reactivity with different MAs loadings, the neutron spectrum shift, the time evolution of MAs and major nuclides inventories, and the transmutation ratio (TR). The TR of the long-lived MAs is calculated by using the SERPENT-2 Monte-Carlo code. The total neutron flux in the SD-TMSR and SMSFR can reach 4.1 × 10 14 and 1.8 × 10 15 n.cm −2 .s −1, respectively. The results show that the SD-TMSR consumes about 50% of the generated Pu isotopes in the fuel salt, however, the SMSFR consumes about 86.5% of the generated Pu isotopes. During burnup, we apply the online reprocessing and refueling, therefore, the core is maintained critical and the total fuel mass in the core and blanket is almost constant. The results demonstrate that both reactors effectively transmute 237 Np, 241 Am, 243 Am, and 243 Cm, meanwhile, the SMSFR has a higher TR than the SD-TMSR. The TR of the total MAs reaches 54.84% and 87.97% in the SD-TMSR and SMSFR, respectively.